دوافع السياسة التركية تجاه الانضمام للاتحاد الأوروبي - رعد خالد; سبور فراس (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The Turkish relations with the European countries is built on the basis of mutual interests, Turkey was, seeks, through participation in economic organizations and military alliances and develop its relations with the West to get economic aid, as well as political support to strengthen the status and clout in the region. Turkish governments have wished to differ in that integrate Turkey fully in Europe through its accession to the European Union, in contrast, Western countries have found it necessary to contain Turkey and annexed before it became part of the socialist camp, which is the dangers that can be faced by European countries and interests in the Middle East by the Soviet Union, as a result of the components of power enjoyed by Turkey, it has a strong army, and if you Teamed with Western countries to be a deterrent to these threats. For this, Turkey has tried to invest in order to achieve their interests and objectives to be a European country, and to achieve a superior or a balanced element positioned to perform a strategic role at least as important as its rivals in Europe such as Greece, for example. إن العلاقات التركية مع الدول الأوروبية بُنيت على أساس المصالح المتبادلة، فتركيا كانت تسعى، من خلال الاشتراك في المنظمات الاقتصادية والأحلاف العسكرية وتطوير علاقاتها بالغرب، إلى الحصول على المساعدات الاقتصادية، فضلاً عن الدعم السياسي لتقوية مركزها وثقلها في المنطقة. فقد رغبت الحكومات التركية على اختلافها في أن تدمج تركيا كلياً في أوروبا عن طريق انضمامها إلى الاتحاد الأوروبي، في المقابل رأت الدول الغربية أنه من الضروري احتواء تركيا وضمها قبل أن تصبح جزءاً من المعسكر الاشتراكي، مما يبعد الأخطار التي يمكن أن تتعرض لها الدول الأوروبية ومصالحها في منطقة الشرق الأوسط من قبل الاتحاد السوفياتي، نتيجة لمكونات القوة التي تتمتع بها تركيا، فهي تمتلك جيشاً قوياً، ويمكن إذا ماتحالفت مع الدول الغربية أن تكون عامل ردع إزاء هذه التهديدات. لهذا، حاولت تركيا أن تستثمر ذلك لتحقيق مصالحها وأهدافها في أن تكون دولة أوروبية، ولتحقيق عنصر متفوق أو متوازن يؤهلها لأداء دور استراتيجي لايقل أهمية عن منافساتها في القارة الأوروبية كاليونان مثلاً.